2014
DOI: 10.22206/cys.2014.v39i4.pp641-663
|View full text |Cite
|
Sign up to set email alerts
|

Tendencias del postgrado en Iberoamérica

Abstract: Ante todo, quisiera anticipar que mi intervención 2 [en este evento] debiera constituir un pequeño pero significativo desarrollo de los planteamientos que he tenido oportunidad de hacer en varios escenarios académicos y advertir que, aunque siguen siendo válidos, tenemos mucho camino aún, por recorrer. La radiografía que he intentado describir ha sido, sin duda, la de un escenario catastrófico pero con matices optimistas, realista, por decir lo menos, pero viable, si quienes asumimos alguna responsabilidad por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…These investigations, although they allow the graduation of the student, do not contain relevant results, and are often published in journals of little scientific level. An important factor that has contributed to this is the global trend that has been manifested since the beginning of the millennium towards reducing the duration of master's programs to one year (Cruz, 2014).…”
Section: The Competitive Approach Vs the Humanist-social Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…These investigations, although they allow the graduation of the student, do not contain relevant results, and are often published in journals of little scientific level. An important factor that has contributed to this is the global trend that has been manifested since the beginning of the millennium towards reducing the duration of master's programs to one year (Cruz, 2014).…”
Section: The Competitive Approach Vs the Humanist-social Approachmentioning
confidence: 99%
“…It is not a question of introducing radical changes in the way in which the postgraduate studies are projected and managed, but of making the purposes indicated in the programs that are approved, in terms such as interdisciplinary approach to the object of knowledge, link with the productive environment, collaborative work (Cruz, 2014) and others, stop being good intentions and become real work objectives. These transformative actions should be accompanied by an accreditation system that gives a greater role to linking postgraduates with society and solving their problems at a local, regional and national level, as well as a forensic fight so that these criteria gain space in global accreditation systems.…”
Section: The Competitive Approach Vs the Humanist-social Approachmentioning
confidence: 99%
“…En la amplia revisión bibliográfica realizada de textos nacionales e internacionales, sobre todo en Iberoamérica, la formación posgraduada es sistematizada por autores como Hatím (1998), Espí (2004), Vecino (2004), Morles (2005), Borges (2006Borges ( ), Álvarez et al (2012, Cruz (2014), Vaillant (2013, Albuja (2017), Figueroa (2017), Tardo (2017), Documentos del MES (2020d) los cuales analizan la formación posgraduada en virtud de las necesidades de la ciencia, tecnología e innovación, concediéndole importancia a la formación científica de los profesores como elemento clave para su desarrollo y desempeño profesional. Sin embargo, estos estudios no se orientan en función de la profesionalización en propiedad intelectual del profesor universitario.…”
unclassified